Three‐Dimensional Electroanatomic Mapping System‐Enhanced Cardiac Resynchronization Therapy Device Implantation: Results From a Multicenter Registry. (19th December 2016) - DEL GRECO, MAURIZIO; MAINES, MASSIMILIANO; MARINI, MASSIMILIANO; COLELLA, ANDREA; ZECCHIN, MASSIMO; VITALI‐SERDOZ, LAURA; BLANDINO, ALESSANDRO; BARBONAGLIA, LORELLA; ALLOCCA, GIUSEPPE; MUREDDU, ROBERTO; MARENNA, BIONDINO; ROSSI, PAOLO; et al.
Electroanatomic Mapping for CRT Implantation Registry: Introduction: Cardiac resynchronization therapy (CRT) device implantation guided by an electroanatomic mapping system (EAMS) is an emerging technique that may reduce fluoroscopy and angiography use and provide information on coronary sinus (CS) electrical activation. We evaluated the outcome of the EAMS‐guided CRT implantation technique in a multicenter registry. Methods: During the period 2011–2014 we enrolled 125 patients (80% males, age 74 [71–77] years) who underwent CRT implantation by using the EnSite system to create geometric models of the patient's cardiac chambers, build activation mapping of the CS, and guide leads positioning. Two hundred and fifty patients undergoing traditional CRT implantation served as controls. Success and complication rates, fluoroscopy and total procedure times in the overall study population and according to center experience were collected. Centers that performed ≥10 were defined as highly experienced. Results: Left ventricular lead implantation was successful in 122 (98%) cases and 242 (97%) controls (P = 0.76). Median fluoroscopy time was 4.1 (0.3–10.4) minutes in cases versus 16 (11–26) minutes in controls (P < 0.001). Coronary sinus angiography was performed in 33 (26%) cases and 208 (83%) controls (P < 0.001). Complications occurred in 5 (4%) cases and 17 (7%) controls (P = 0.28). Median fluoroscopy time (median 11 minutes vs. 3 minutes, P < 0.001) and CS angiography rate (55% vs. 21%, P < 0.001) were significantly higher in low experienced centers, while success rate and complications rate were similar. Conclusions: EAMS‐guided CRT implantation proved safe and effective in both high‐ and low‐experienced centers and allowed to reduce fluoroscopy use by ≈75% and angiography rate by ≈70%.